Men writing eating disorders : autobiographical writing and illness experience in English and German narratives - Bartel, Heike (Bingley, U.K. : Emerald Publishing Limited, 2020)
Eating disorders do not only affect women and girls; men and boys get them too but remain mostly invisible. This book gives insight into this neglected problem through a comparative and transnational analysis of autobiographical accounts written by men with experience of living with eating disorders.
Prelims -- Introduction -- 1: Eating disorders and men -- 2: Constructing eating disorders -- 3: Written on the body -- 4: Autobiographical writing -- 5: Writing for healthcare -- Conclusion -- Bibliography -- Index.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: English literature -- Male authors -- History and criticism; German literature -- Male authors -- History and criticism; Autobiography; Eating disorders in men; Eating disorders in literature; Masculinity in literature; Mental illness in literature; Literary Collections -- European / English, Irish, Scottish, Welsh; Literary studies: fiction, novelists & prose writers